Biphasic hierarchical extracellular matrix scaffold for osteochondral defect regeneration. Issue 3 (March 2018) - Lin, X.; Chen, J.; Qiu, P.; Zhang, Q.; Wang, S.; Su, M.; Chen, Y.; Jin, K.; Qin, A.; Fan, S.; Chen, P.; Zhao, X.
Summary: Objective: To investigate the effect of decellularized osteochondral extracellular matrix (ECM) scaffold for osteochondral defect regeneration. Design: We compared the histological features and microstructure of degenerated cartilage to normal articular cartilage. We also generated and evaluated osteochondral ECM scaffolds through decellularization technology. Then scaffolds were implanted to osteochondral defect in rabbit model. After 12 weeks surgery, regeneration tissues were analyzed by histology, immunohistochemistry evaluation. And possible mechanisms of angiogenesis and cell migration were explored. Results: We demonstrated decreased cell numbers, formation of fibrous cartilage, lost microstructure and worse permeability in degenerated cartilage compared to normal cartilage. We also generated an osteochondral ECM scaffold with a hierarchical structure that exhibited low immunogenicity, high bioactivity, and well biocompatibility. We found that the ECM scaffold promoted tissue regeneration in osteochondral defects, which was dependent on the scaffold constituents and stratified three-dimensional microstructure as well as on its ability to inhibit angiogenesis and stimulate cell migration. Conclusions: Our findings demonstrated that the biphasic hierarchical ECM scaffold represents a novel and effective biomaterial that can be used in the treatment of osteochondral defect.